Are BBQs Significantly Polluting Air in Poland? A Simple Comparison of Barbecues vs. Domestic Stoves and Boilers Emissions - Artur Badyda; Piotr Krawczyk; Jan Stefan Bihałowicz; Karolina Bralewska; Wioletta Rogula-Kozłowska; Grzegorz Majewski; Przemysław Oberbek; Andrzej Marciniak; Mariusz Rogulski (Energies, 2020)
The study attempts to compare the total annual emissions of selected air pollutants emitted during occasional grilling and the emission of the same pollutants from small domestic heating installations. For this purpose, in the absence of any data on the emission of pollutants during grilling processes, tests were carried out consisting of measuring the concentration of air pollutants in exhaust streams from two types of grills (solid fuel grill powered by charcoal briquette and gas grill powered by liquid propane), using popularly prepared dishes (previously marinated meat and raw, seasoned mixed vegetables). The concentrations of PM2.5, CH4, CO, CO2, H2O, NH3, N2O, NO, NO2, SO2 were measured in the exhaust stream from both grills using a particulate matter (PM) measuring device and a portable spectrometer, separately while grilling the same portions of meat and vegetables. Then, considering the available data on Poles’ barbecue habits, the emissions that are released into the air during occasional grilling were estimated. The calculated emissions were compared with the data on emissions from domestic heating installations used in Poland. It has been shown that during grilling, as much as 2.30, 92.07, 4.11, 3.83, 2.96, and 9.81 Gg of PM2.5, CO, NOx, SO2, NH3, and CH4 may be released into the atmosphere in Poland, respectively. In the case of PM, the amount of the pollutant emitted to the air is over 100 times lower than the emissions caused by the operation of small heating installations. In the case of other pollutants, the differences are smaller. Nevertheless, emissions from grills should not be underestimated as, in certain periods of the year, these sources may be responsible for not meeting the air quality standards in selected areas of the country, and thus the excessive exposure of people to pollutants resulting in negative health consequences. Therefore, attention was paid to the legitimacy of abandoning the use of charcoal and charcoal briquette grills and replacing them with gas-powered grills or electric ones, not only due to the health benefits of food and lower human exposure, but also by the reason of ecological values.